Correlation of Student Learning Activities and Cognitive Learning Outcomes Using Problem-Based Learning - Sholihah, Fatikhatun Nikmatus; Rahayu, Siti; Wahyudi, Muhammad Zainal Dwi (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study aims to analyze the relationship between student learning activities and cognitive learning outcomes through the application of the Problem-Based Learning (PBL) model to ecosystem material. The study used a quantitative approach with a correlational design. The study population was all 10th-grade students of Mojoagung State Senior High School, Jombang, with a sample of 36 10th-grade students selected using a purposive sampling technique. Data on student learning activities were obtained through observation sheets, while cognitive learning outcomes were measured using a learning achievement test. Data analysis was performed using the Spearman correlation test using SPSS version 26 software. This is because the learning activity data is ordinal in scale. The results showed that there was a positive and significant correlation between student learning activities and cognitive learning outcomes with a Spearman correlation coefficient of 0.943 and a significance value of 0.000 (p < 0.05), which is in the very strong relationship category. This finding indicates that the higher the student learning activities in problem-based learning, the higher the cognitive learning outcomes achieved. The implications of this study confirm that the application of PBL which emphasizes active student involvement plays an important role in improving conceptual understanding, especially in ecosystem material which is complex and contextual.